Genetic variation among the geographic population of Cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae) in Indonesia inferred from mitochondrial COI gene sequence (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nopriawansyah N, Rauf A, Kusumah YM, Nurmansyah A, Koesmaryono Y. 2019. Genetic variation among the geographic population of Cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae) in Indonesia inferred from mitochondrial COI gene sequence. Biodiversitas 20: 2685-2692. Cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) is an invasive pest native to South America. Research was conducted with the objective to study genetic variation of cassava mealybug from different geographic areas in Indonesia. Thirty-six samples of cassava mealybugs were collected from eight different population locations. Genomic DNA was extracted from individual specimens of P. manihoti using gSYNC DNA Extraction Kit from Geneaid Lot No. FB221707. PCR amplification using primary CO1 gene showed the target position as long as 518 bp. Analysis of homology from eight populations revealed eight haplotypes in Indonesia with different variable sites. Genetic distance analysis was done by calculating base pair differences in each population. The percentage of genetic distance between populations was 0.0000% -0.00409%. The results of the analyst using the Kimura-2 parameter showed that the population was divided into 2 clusters. The highest haplotype (Hd) diversity value was 0.8333, while the lowest was zero (Hd = 0). The highest nucleotide diversity (?) was 0.00225 and the lowest was 0.000000. The genetic distance and nucleotide diversity were low because P. manihoti was thelytoky parthenogenesis.
Keywords: Cassava mealybug , CO1, genetic diversity, Phenacoccus manihoti